Education on the Use of Digital Comics as an Alternative Learning Media for Pancasila Education Values and Morals - Alfan Bramantya; Eko Pujiati; Shofiyatul Azmi; Reynaldi Arya Putera Kusuma; Amalia Nur Fauziah; Anna Susanti; Ardika Rizki Pranoto Utomo (Journal of Community Service and Empowerment, 2025)
Empowering the values and moral education in the Pancasila Education subject often experiences problems from a lack of student participation and attention because learning methods are considered monotonous. Community service programs targeting eighth-grade students at SMP PGRI 01 Dau aim to provide insight into the use of digital comics as an alternative learning medium that is contextual and interesting and in accordance with the character of a generation digitally. The strategy adopted the PIMA (preparation, implementation, monitoring, and appraisal) model that includes needs assessment, educational workshops, student response feedback, and impact evaluation. The results showed that digital comics effectively enhanced students’ understanding of noble national values such as mutual cooperation, tolerance, honesty, and responsibility. Reflective questionnaires showed that more than 85 percent of students felt that moral values in digital comic stories were easier to understand and apply. The initiative has also had a beneficial effect on students' motivation to adopt ethical conduct and in consolidating their national identity. This medium of digital comics became fun and transformational because visual narratives made the core value-based ideology easily digestible. There are commonalities to constructivist theory, contextual learning models, and dual coding theory, all of which can be clearly related to character education supported by technology. Considering the aforementioned, digital comics are suggested to be a novel approach for value-based learning in secondary schools.